Analysis of Static Code Techniques for Vulnerability Detection: A reviewed Literature - Musyoka, Faith M. (My University, 2017)
Web applications have become an integral part of the daily lives of trillions of users. These systems are usually complex and are developed by different programmers. Regularly programmers make mistakes in the code which could generate critical software vulnerabilities. Despite the knowledge about vulnerabilities nowadays there is still a growing tendency in the number of reported vulnerabilities, reason why software security has become an important field of research. Due to the presence of vulnerabilities it has been necessary to have tools that can help programmers detect them in code development stage. This paper has analysed pattern matching and taints analysis techniques that are currently used in development of static tools to in detection of vulnerabilities.
Keywords: static code analysis techniques; vulnerability; taint analysis; pattern matching